Analysis of Election Results Data Transparency as an Instrument for Protecting Citizens' Constitutional Rights - Asyam Haidar Fathin (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the transparency of election result data as an instrument for protecting the constitutional rights of citizens within Indonesia’s constitutional system. This research employed a normative legal method with a descriptive-analytical approach, using statutory, conceptual, and case approaches. The legal materials consisted of primary, secondary, and tertiary legal sources collected through library research and document study, which were then analyzed qualitatively. The results show that the transparency of election result data has a strong constitutional and juridical foundation, particularly in the principles of popular sovereignty, the right to information, and the accountability of election administration. However, its implementation in the digital era still faces several problems, including fragmented portals, system inaccuracies, limited public access, weak data updating, and tensions between information disclosure and personal data protection. Therefore, strengthening the transparency of election result data requires regulatory harmonization, integrated data governance, stronger audit trails and verification mechanisms, improved capacity of public information management officers, more user-friendly data presentation, and institutionalized public participation so that transparency can genuinely function as an instrument for protecting citizens’ constitutional rights.